2023
DOI: 10.3390/pathogens12010118
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Polymicrobial Community Biofilm Model Demonstrates Spatial Partitioning, Tolerance to Antimicrobial Treatment, Reduced Metabolism, and Small Colony Variants Typical of Chronic Wound Biofilms

Abstract: Understanding chronic wound infection is key for successful treatment and requires accurate laboratory models. We describe a modified biofilm flow device that effectively mimics the chronic wound environment, including simulated wound fluid, a collagen-based 3D biofilm matrix, and a five-species mixture of clinically relevant bacteria (Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Enterococcus faecalis, and Citrobacter freundii). Mixed biofilms were cultured for between 3 and 14 days with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Previous research indicates that within wound environments, anaerobic bacteria tend to inhabit the middle region, sustained by oxygen consumers (Choi et al, 2019). Compelling in vivo evidence supports the notion that P. aeruginosa predominantly colonizes the deeper layers of wounds, while S. aureus tends to establish itself on the wound's surface (Fazli et al, 2009;Chen et al, 2021;Khalid et al, 2023). Pouget et al, showed aggregated biofilms of both S. aureus and P. aeruginosa at the specific locations still maintaining a mixed polymicrobial biofilm with enhanced characteristics (Pouget et al, 2022).…”
Section: Polymicrobial Niche Colonizationmentioning
confidence: 82%
“…Previous research indicates that within wound environments, anaerobic bacteria tend to inhabit the middle region, sustained by oxygen consumers (Choi et al, 2019). Compelling in vivo evidence supports the notion that P. aeruginosa predominantly colonizes the deeper layers of wounds, while S. aureus tends to establish itself on the wound's surface (Fazli et al, 2009;Chen et al, 2021;Khalid et al, 2023). Pouget et al, showed aggregated biofilms of both S. aureus and P. aeruginosa at the specific locations still maintaining a mixed polymicrobial biofilm with enhanced characteristics (Pouget et al, 2022).…”
Section: Polymicrobial Niche Colonizationmentioning
confidence: 82%
“…In chronic wound infections, biofilms consisting of S. aureus and P. aeruginosa are commonly found together leading to delayed healing and persistent infections (Borges et al, 2022). Laboratory models developed to monitor biofilm colonization in chronic wounds and biopsies reveal that bacteria form species specific aggregates in distinct regions of the tissue (Khalid et al, 2023). Real-time detection of volatile metabolites can be used to discriminate between different microbial species in biofilms (Slade et al, 2022).…”
Section: Woundsmentioning
confidence: 99%